Mechanism of transmembrane and long-distance transport of nickel in higher plants - Mackievic, Viera S.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2023)
Nickel (Ni2+ ) is an indispensable element of mineral nutrition in plants, which is needed for the normal course of physiological processes in very small quantities. In high concentrations, this heavy metal is harmful to metabolism and causes a pronounced toxic effect. In recent years, a number of works have appeared devoted to the study of Ni2+  accumulation, distribution and translocation in the tissues of higher plants. It has been established that Ni2+  uptake can be carried out by passive or active transfer through the plasma membrane of root cells. Passive transport is mediated through non-selective cation channels, with members of the cyclic nucleotide-gated channel (CNGC) family probably contributing the most. Active transport occurs with the participation of special transporter proteins, primarily ZIP (zinc-regulated, iron-regulated transporter-like proteins), which has so far been experimentally demonstrated for IRT1 (iron-regulated transporter-like proteins). Ni2+  is loaded into the xylem and redistributed to various plant organs and tissues by active transporters ZIP, HMA (P1B-type heavy metal ATPases) and NRAMP (natural resistance-associated macrophage proteins). This process is influenced by the synthesis and concentration of complexing agents such as histidine, nicotinamine, glutathione, phytochelatins, phenols and organic acids. Further studies in the field of Ni2+  transport will probably focus on the identification of subunits of non-selective cation channels responsible for the entry of nickel into the plant root cells, and the identification of the relations between transport processes and their regulation at the posttranscriptional and posttranslational levels.
Keywords: nickel; cation channels; active transport; higher plants